Acellular Dermal Matrix Sterility: Does It Affect Microbial and Clinical Outcomes Following Implantation?. Issue 8 (August 2019) - Klein, Gabriel M.; Singh, Gurtej; Marquez, Jocellie; Gebre, Matthew; Barry, Robert; Huston, Tara L.; Ganz, Jason C.; Khan, Sami U.; Dagum, Alexander B.; Bui, Duc T.
Abstract : Introduction: The use of acellular dermal matrices (ADMs) in breast reconstruction is a controversial topic. Recent literature has investigated the effects of ADM sterilization on infectious complications, although with varying conclusions. Previous work by our group showed no difference between aseptic and sterilized products immediately out of the package. In this study, we investigate the microbiologic profiles of these agents after implantation. Methods: In this prospective study, we cultured samples of ADM previously implanted during the first stage of tissue expander-based immediate breast reconstruction. A 1 cm2 sample was excised during the stage II expander–implant exchange procedure, and samples were incubated for 48 hours in tryptic soy broth. Samples with growth were further cultured on tryptic soy broth and blood agar plates. Patient records were also analyzed, to determine if ADM sterilization and microbial growth were correlated with infectious complications. Results: In total, 51 samples of ADM were collected from 32 patients. Six samples were from aseptic ADM (AlloDerm), 27 samples were from ADM sterilized to 10–3 (AlloDerm Ready-to-Use), and 18 samples were from products sterilized to 10–6 (AlloMax). No samples demonstrated bacterial growth. Only 5 patients experienced postoperative complications, of whom only 1 patient was infectious in nature. We failed to demonstrate a statistically significant correlation between sterility and postoperative complications. Conclusions: Our findings showed no difference in microbial presence and clinical outcomes when comparing ADM sterility. Furthermore, no samples demonstrated growth in culture. Our study brings into question the necessity for terminal sterilization in these products.